2022
DOI: 10.1080/0886022x.2022.2087527
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and risk factors in elderly patients with biopsy-proven IgA nephropathy

Abstract: Background Immunoglobulin A nephropathy (IgAN) has been well studied among young people, but few data on clinicopathological characteristics, treatment response and outcomes for elderly IgAN patients are available. Methods A cohort study of elderly IgAN patients was performed. The combined endpoints of renal outcome were a 50% decline in eGFR compared with the time of renal biopsy, end-stage kidney disease and/or death. Risk factors associated with poor renal outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…During their follow-up, renal survival rates of male IgAN patients were significantly lower than female patients (17). Consistently, other studies found that being male was associated with greater levels of serum creatinine and a worse outcome (17,18). An analysis by Riispere et al on 73 biopsy-proven IgAN cases (62% males and 38% females) held the same view that IgAN progresses more rapidly in male than in female patients through faster glomerular filtration rate declines.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…During their follow-up, renal survival rates of male IgAN patients were significantly lower than female patients (17). Consistently, other studies found that being male was associated with greater levels of serum creatinine and a worse outcome (17,18). An analysis by Riispere et al on 73 biopsy-proven IgAN cases (62% males and 38% females) held the same view that IgAN progresses more rapidly in male than in female patients through faster glomerular filtration rate declines.…”
Section: Discussionsupporting
confidence: 52%
“…Lv et al demonstrated, proteinuria of more than 1 g/d connected to poor prognosis in patients with an average of 6.1 years (23). Contrary to these results, Sevillano et al in a cohort of 151 patients ≥65 years old, and Tan et al on 126 patients with a mean age of 57.12 ± 6.24 years, reported proteinuria was not significantly associated with poor outcomes (16,18). We suggest that the disparity between these studies can be due to several variables, including the patient population, the duration of follow-up, age, behavioral patterns such as individual physical activity or eating habits, race, biopsy practice, and various outcome definitions.…”
Section: Discussionmentioning
confidence: 94%
“…2). The decrease in these indicators was found to be associated with a poor prognosis in previous studies [17,18]. However, the multivariate Cox proportional hazards model showed that the crescent was not an independent risk factor.…”
Section: Discussionmentioning
confidence: 71%
“…IgAN accounts for ~40% of all native-kidney biopsies in Japan, 25% in Europe and 12% in the United States ( 56 , 57 ). Currently, the gold standard for the diagnosis of IgAN remains renal biopsy, which, as an invasive diagnostic method, has numerous limitations and may lead to multiple complications ( 58 , 59 ). Traditional clinicopathological indicators remain inadequate to predict the diagnosis, progression and prognosis of IgAN, such as blood pressure, albuminuria and hematuria.…”
Section: Discussionmentioning
confidence: 99%